2019
DOI: 10.7717/peerj.7261
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic and proteomic analyses of the green and white parts of chimeric leaves in Ananas comosus var. bracteatus

Abstract: Background Ananas comosus var. bracteatus has high ornamental value due to its chimeric leaves. However, the chimeric trait is very unstable in red pineapple plants, and transcriptional variation between the two types of cells (white/green cells) and the molecular mechanism responsible for their albino phenotype remain poorly understood. Methods Comparative transcriptomic and proteomic analyses of the white parts (Whs) and green parts (Grs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…These results suggested that the function of photosynthesis and energy metabolism might be suppressed in the Wh parts of chimeric leaves. This is accordance with our comparative proteomic data studied previously [13].…”
Section: The Proteome Profile Was Altered In the Wh Parts Of Chimericsupporting
confidence: 94%
See 3 more Smart Citations
“…These results suggested that the function of photosynthesis and energy metabolism might be suppressed in the Wh parts of chimeric leaves. This is accordance with our comparative proteomic data studied previously [13].…”
Section: The Proteome Profile Was Altered In the Wh Parts Of Chimericsupporting
confidence: 94%
“…Whereas upregulated proteins in the Wh parts were mainly enriched in spliceosome and ribosome through previous study [13]. Proteins with downregulated Ksu sites in the Wh parts were enriched in pathways involving the CAC, carbon metabolism, glyoxylate metabolism, dicarboxylate metabolism, pyruvate metabolism, and 1oxocarboxylic acid metabolism.…”
Section: The Succinylome Profile Was Changed In the Wh Parts Of Chimementioning
confidence: 58%
See 2 more Smart Citations
“…During spring and autumn, the leaves will appear bright red, which improved a lot in ornamental value of Ananas comosus var. bracteatus [19]. However, in summer and winter, the redness of the leaves gradually fades, returning to green/white.…”
Section: Introductionmentioning
confidence: 99%